Oral hygiene habits among Polish students of dentistry, medicine and the students of English Division of Medical University of Lublin - Wilczyńska, Karolina; Książek, Katarzyna; Pietrak, Justyna; Maślanko, Monika; Wilczyński, Michał; Jankowski, Karol; Wójtowicz, Wioleta; Pels, Elżbieta; Mielnik-Błaszczak, Maria (Polish Journal of Public Health, 2013)
Introduction. Proper oral hygiene has a significant effect on the health of the entire body, but frequent brushing of teeth and proper diet can substantially reduce dental caries risks.Aim. The aim of the work is the comparison of oral hygiene habits among Polish and foreign students of Medical University of Lublin.Material and methods. We have carried out a survey among 279 Students of Medical University of Lublin. The respondents comprised 189 students from Poland and 90 students of English Division who come from USA, Canada, Taiwan, India, and Norway. The survey questions concerned the frequency of tooth brushing, consumption of sweets, and dental office visits. The results were statistically analysed.Results. The results are summarized in Tables 1-5. The respondents were divided into two groups: Polish and foreign students. Statistical analysis has revealed statistically significant difference between Polish and foreign students concerning the frequency of dental office visits, brushing teeth, tongue cleaning, and subjective evaluation of oral health condition. There is no statistically significant difference in frequency of sweets consumption.Discussion. Research results concerning oral health care awareness of the students of Medical University of Lublin were compared to the results of Kawamura from Hiroshima, Usman from India, Wędrychowicz-Welman from Poznań, among others.Conclusions. Students of Medical University of Lublin demonstrate sufficient level of oral health awareness. Foreign students visit dental office more often to check-up their teeth. Both groups of respondents usually brush their teeth two times a day, regularly clean tongue and evaluate their oral health condition as good.